ATRT-05. Infants and newborns with atypical teratoid/rhabdoid tumors (ATRT) and extracranial malignant rhabdoid tumors: a unique and challenging population. (3rd June 2022) - Nemes, Karolina; Johann, Pascal D; Steinbügl, Mona; Gruhle, Miriam; Bens, Susanne; Kachanov, Denis; Teleshova, Margarita; Peter, Hauser; Simon, Thorsten; Tippelt, Stephan; Eberl, Wolfgang; Chada, Martin; et al.
Abstract: INTRODUCTION: Malignant rhabdoid tumors (MRT) predominantly affect infants. Patients below six months represent a particularly challenging group: intensity of therapy is limited by toxicity to developing organs. Information on prognostic factors, toxicity and long term outcome is sparse. METHODS: Clinical, genetic, and treatment data of 100 patients (less than 6 months at diagnosis) from 13 European countries were analyzed (2005-2020). Tumors and matching blood samples were examined for SMARCB1 mutations using FISH, MLPA and Sanger sequencing. DNA-methylation subgroups (ATRT-TYR, ATRT-SHH, and ATRT-MYC) were determined using DNA methylation arrays. RESULTS: A total of 45 patients presented with ATRT, 29 with extracranial, extrarenal (eMRT) and 9 with renal rhabdoid tumors (RTK). Seventeen patients demonstrated synchronous tumors (SYN). Distant metastases at diagnosis (M+) were present in 27% (26/97). A germline mutation (GLM) was detected in 55% (47/86). Methylation subgroup status was available in 50% (31/62) of ATRT or SYN (SHH=13, TYR=13, MYC=4, SHH+TYR=1). The 5-year overall- (OS) and event free survival (EFS) rates were 23.5±4.6% and 19±4.1%, respectively. Male sex (11±5% vs. 35.8±7.4%), M+ (6.1±5.4% vs. 36.2±7.4%), presence of SYN (7.1±6.9% vs. 26.6±5.3%) and -GLM (7.7±4.2% vs. 45.7±8.6%) were significant prognosticators of 5-year OS, in univariate analysis. Molecular subgroup and survival analyses confirmed the previously described survival advantage of ATRT-TYR. In an adjusted multivariate model clinical factors that influence prognosis were: male sex [HR: 2.1 (1.2 – 3.6)], M+ [3.3 (1.8 – 6)], GLM [HR: 2 (1.1 – 3.6)] and maintenance therapy [HR: 0.3 (0.1 – 0.8)]. CONCLUSION: In this large cohort of homogenously treated infants with MRT, significant predictors of outcome were sex, M+, GLM and maintenance therapy. We confirm the need to stratify which patient group benefits from multimodal treatment, and which patients need novel therapeutic strategies. Biomarker-driven tailored trials may be a key option.